The Influence of Parental Attention on Mathematics Learning Outcomes of Grade IX Students at Cinta Rakyat 3 Private Middle School, Pematang Siantar - Simanjuntak, Lasmaria R; Sidabutar, Ropinus (EduMatika: Jurnal MIPA, 2024)
This study aims to determine whether there is an influence of parental attention on the mathematics learning outcomes of class IX students at SMP Swasta Cinta Rakyat 3 Pematang Siantar. This study uses a quantitative approach, the type of research used in this study is ex post facto. The population in this study were all class IX students of SMP Swasta Cinta Rakyat 3 Pematang Siantar in the 2023/2024 academic year totaling 149 students. In sampling, the researcher used Cluster random sampling in this study, the researcher took one class, namely IX-A, so the total sample in this study was 37 students. Data were obtained from the parental attention questionnaire instrument and from document data on the mathematics learning outcomes of class IX students of SMP Swasta Cinta Rakyat 3 Pematang Siantar. The instruments used were 30 closed statement questionnaires, using a Likert scale measurement. After the calculation, the conclusion of the calculation on simple linear regression with the equation Y' = a + b X = 39.837 + 0.371X with a calculated t value = 12.412 > t table = 2.0262 with a significance level of 0.00 < 0.005. So H0 is rejected and Ha is accepted. The influence of parental attention on students' mathematics learning outcomes in class IX of SMP Swasta Cinta Rakyat 3 Pematang Siantar is 82%, which means that parental attention can influence students' mathematics learning outcomes by 82%, where another 18% can be influenced by other factors.